Study on Cyber Safety Awareness among Malaysian Primary Students A Case Study: QR Code Game in SK Bangi - Abd Rahman, Nor Azlina; Zainal Abidin, Zety Marlia (International Journal of Psychosocial Rehabilitation, 2019)
This paper explore the coverage and exposure towards the cyber safety awareness among primary school student in Malaysia and later present a study on the practical approach in infusing the cyber safety awareness through multiple platform in increasing the level of understanding of the student about the matter. QR code technology was used as a platform to engage with the students and develop interesting learning environment where the students will involve in activities rather than just sitting and listening to the lecture or talk. Mix method was used and the sample consisted of 5 teachers and 50 children aged 10-11 years old in a primary school. As data collection tools, an observation and interview form were used. The qualitative methodology are used in observing the primary student exposures towards the knowledge on regards of the security risks and threat and the understanding on how the student react and overcome those issues. The findings and recommendation from this study are fundamental in enhancing the approach in delivering the cyber safety awareness to the student apart from only using the school as the medium